The effectiveness of intergovernmental relations in the Northern Cape Provincial Government, with focus on the Premier’s Intergovernmental Forum - Gaoretelelwe, Moipolai Percival (University of the Free State, 2017)
No abstract included
Dissertation (MGT (Governance and Political Transformation))--University of the Free State, 2017
Keywords: Intergovernmental relations -- South Africa -- Northern Cape; Local government -- South Africa -- Northern Cape